Digital Platforms For Inclusive Scaling Of Climate Information Services: Insights And Lessons Learned From 2022 To 2025 In Mali - Suh, Neville Ndohnwi; Diarra, Afoussatou; Dossou Yovo, Elliott Ronald (2025)
Rice is a vital staple food for most of Mali's population, especially supporting the food and nutritional security of poor rural farming households. However, like other crops, rice production in Mali faces challenges from recurrent extreme weather events such as floods and droughts, which impact yields and worsen food and nutritional insecurity among rural farmers. Of particular concern are the floods that affected several rice-growing villages in the Sikasso and Koulikoro regions during the 2025 rice farming season, destroying entire rice fields. As a result, farmers are likely to face increased food and nutritional insecurity along with livelihood losses in the 2025/2026 agricultural year. Vulnerable farmers respond and adapt differently to floods depending on whether they are using climate information services (CIS) promoted by AICCRA to guide their farming practices and whether they are using flood-tolerant rice varieties informed by digital climate advisories platforms. Farmers who benefited from CIS promoted by AICCRA Mali experienced less severe impacts from the flood, highlighting the importance of continuing to scale these CIS across rice production in Mali with the aim of sustained climate resilience. Moreover, between 2022 and 2025, over 498,220 farmers (16% of whom are women) are using tailored CIS promoted by AICCRA Mali for rice farming. The main goal of this workshop is to strengthen the capacity of various actors involved in rice value chains to use CIS via different digital platforms to inform their rice production decisions. The workshop also identified various barriers to adopting these CIS across different platforms. To strengthen the ongoing scaling of the AICCRA initiative, key lessons and insights from implementing the project from 2022 to 2025 will be identified, which are essential to promoting sustained dissemination of CIS in rice production in Mali.